Formal and informal ways of learning in employer-provided further training in East and West German enterprises: Results from a large-scale establishment survey - Martin Brussig; Ute Leber (Journal for East European Management Studies, 2006)
The paper analyses the mix of training forms in employer-provided training in East and West German enterprises with a special emphasis on informal and work-integrated forms of learning. Recent studies have shown that East German enterprises are at least as active in employer-provided training as West German firms. However, these studies are limited to formal ways of further training. Based on a large-scale enterprise survey and ordered-logit regressions, differences in employer-provided further training activities between East and West German enterprises can be shown. In particular, East German enterprises are less active in informal and work-integrated ways of further training. – – Der Beitrag untersucht die unterschiedlichen Formen betrieblicher Weiterbildung mit einer besonderen Betonung der informellen und arbeitsintegrierten Formen betrieblicher Weiterbildung im Ost-West-Vergleich. Frühere Studien haben gezeigt, dass ostdeutsche Firmen mindestens so aktiv in betrieblicher Weiterbildung sind wie westdeutsche Betriebe. Jedoch beschränkten sich diese Studien auf formelle Formen betrieblicher Weiterbildung. Basierend auf einer großen Betriebsbefragung und orderedlogit- Schätzungen können Unterschiede in betrieblichen Weiterbildungsaktivitäten zwischen ostdeutschen und westdeutschen Betrieben nachgewiesen werden.
Keywords: 650; employer-provided further training; informal and work-integrated learning; human resource management